2010
DOI: 10.1002/path.2683
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations and losses of expression of microRNA regulation‐related genes AGO2 and TNRC6A in gastric and colorectal cancers

Abstract: Mounting evidence indicates that deregulation of microRNAs (miRNAs) are involved in development of many human diseases, including cancers. Regulation of miRNA is a complicated process and some components in the regulation are known to be altered in human cancers. Among the miRNA regulation-related genes, we found that AGO1, AGO2, TNRC6A, TNRC6C, TARBP2 and EXPORTIN5 genes have mononucleotide repeats in their coding sequences. To see whether these genes are mutated in cancers with microsatellite instability (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 24 publications
2
73
0
Order By: Relevance
“…For example, increased expression levels of miRNAs, Dicer, TRBP, and Ago2 have been shown for prostate cancer cells compared to normal tissue (45). A mutation in the tarbp2 gene was also found in a gastric carcinoma, a cancer with microsatellite instability and a deregulation of miRNA expression (77). Further studies are needed to confirm the relevance and the role of these mutations in cancer development and to determine if TRBP deregulations contribute to additional cancers.…”
Section: Truncated Trbp and Mirna Expressionmentioning
confidence: 99%
“…For example, increased expression levels of miRNAs, Dicer, TRBP, and Ago2 have been shown for prostate cancer cells compared to normal tissue (45). A mutation in the tarbp2 gene was also found in a gastric carcinoma, a cancer with microsatellite instability and a deregulation of miRNA expression (77). Further studies are needed to confirm the relevance and the role of these mutations in cancer development and to determine if TRBP deregulations contribute to additional cancers.…”
Section: Truncated Trbp and Mirna Expressionmentioning
confidence: 99%
“…In gastric cancer, the mRNA and protein expression of Dicer1 are significantly reduced during disease progression (Zheng et al, 2007). In a subset of gastric cancer with high microsatellite instability, Ago2 and TNRC6A, both of which are related to the execution of the gene-silencing function of miRNA, are also mutated and downregulated (Kim et al, 2010). Ago2 is a major component of RNAinduced silencing complex, whereas TNRC6A associates with Ago proteins and the target mRNA to induce gene silencing (Lazzaretti et al, 2009).…”
Section: Dysregulated Mirna In Gastric Cancermentioning
confidence: 99%
“…In addition, other reports showed that low expression levels of Drosha were significantly associated with advanced tumor stage in ovarian cancer [41]. Other components of the microRNA machinery that have been implicated in cancer include Argonaute family members Ago1, Ago3, and Ago4 which cluster on the 1p34-35 chromosomal region, that is often lost in in human cancers such as Wilms tumors, neuroblastoma and breast, liver and colon carcinomas [42]. In summary, emerging evidence suggests that oncomiRs play important roles in human cancers.…”
Section: Micrornas and Cancer: Oncomirsmentioning
confidence: 99%